Z dziejów dramatu biblijnego - o ofiarowaniu Izaaka - Kupisz, Kazimierz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
The story of Abraham and Isaac belongs to the plots frequently recurring in the school drama of sixteenth century Europe. Two related texts are related in the article: Theodore de Bčze’s drama with the title Abraham sacrificanl (staged in Lausanne in 1550) and an anonymous Polish text dating from the end of the sixteenth century Ofiarowanie Izaaka [The Sacrifice of Isaac]. Both the dramas begin with the Prologue, heralding the main events of the story. The works share a three-part, biblical structure (Ofiarowanie Izaaka is composed of three acts), the motif of a father’s love for his son, Abraham’s and Sarah’s care for their son, Abraham’s perplexity and finally the ending, where an angel, a pre-figuration of Christ, appears. The main differences lie in the way in which the protagonists have been grouped - the amusing characters of, among others, Achne, the servant, enrich the play with comical, realistic elements. The similarities between the two texts result not only from their chronology, the common repertoire of school theatres, and the cosmopolitan character of school education. The congruence (despite some apparent differences between the staging possibilities of Lausanne and Cracow) confirms a close relationship between Polish Renaissance drama and the culture of Western Europe and emphasizes its creative character in the presentation of Biblical plots, extending beyond the Bible.